PERTANGGUNGJAWABAN PIDANA BAGI PEMILIK APLIKASI MICHAT SEBAGAI SARANA PROSTITUSI ONLINE - Arvin Dian Ardiansyah; Ahmad Mahyani (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The MiChat Application Developer basically created the MiChat Application as a means of communication, with excess features that make it easier to find new friends who are within a 5-20 km area of ??the vicinity and are not intended as a means of prostitution which is happening a lot now. And it cannot be said that it is also a means of online prostitution because at first the MiChat application was created as an instant messaging application in general that functions for communication. Online prostitution is a human activity that involves sexuality as an object to be used as a field or a place to do business carried out by a handful of individuals to gain profit through wrong and deviant methods through online media. all parties can detect the existence of prostitution cases because they are carried out through media that continues to experience developments such as online media. Indonesia is one of the countries that has experienced very rapid technological developments which have had various impacts, one of which is the negative impact which has made prostitution cases easily accessible, and has become an event that has trapped many women and men in the world of prostitution. Law No. 11 of 2008 concerning Information and Electronic Transactions is the foundation for making online media regulations in preventing cases of prostitution that are currently widespread in electronic crime. In this case, a careful role is needed between the Government and the MiChat application developer in prostitution cases by updating regulations for all applications so that they can anticipate online prostitution cases so that they can facilitate people's efforts to carry out online prostitution